Towards Emulation-as-a-Service: Cloud Services for Versatile Digital Object Access - Dirk von Suchodoletz; Klaus Rechert; Isgandar Valizada (International Journal of Digital Curation, 2013)
The changing world of IT services opens the chance to more tightly integrate digital long-term preservation into systems, both for commercial and end users. The emergence of cloud offerings re-centralizes services, and end users interact with them remotely through standardized (web-)client applications on their various devices. This offers the chance to use partially the same concepts and methods to access obsolete computer environments and allows for more sustainable business processes. In order to provide a large variety of user-friendly remote emulation services, especially in combination with authentic performance and user experience, a distributed system model and architecture is required, suitable to run as a cloud service, allowing for the specialization both of memory institutions and third party service providers.